If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-75=2x(x+15)
We move all terms to the left:
5x-75-(2x(x+15))=0
We calculate terms in parentheses: -(2x(x+15)), so:We get rid of parentheses
2x(x+15)
We multiply parentheses
2x^2+30x
Back to the equation:
-(2x^2+30x)
-2x^2+5x-30x-75=0
We add all the numbers together, and all the variables
-2x^2-25x-75=0
a = -2; b = -25; c = -75;
Δ = b2-4ac
Δ = -252-4·(-2)·(-75)
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{25}=5$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-25)-5}{2*-2}=\frac{20}{-4} =-5 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-25)+5}{2*-2}=\frac{30}{-4} =-7+1/2 $
| 9-10x=2x+8-12x | | 3(8x-6)=25x | | 8(p-17)=3(p+3) | | 31=9(5k+6) | | (8x/x-1)+(1/4)=(7/8)+(8/x-1) | | 4×(3x+1)=52 | | 4n+5+3=-27 | | 8x+12/4=7 | | -8x-11=14-3x | | 5=n=8 | | 14÷z=42 | | 12=n=7 | | 4=x/19 | | 2(x-7)+1=15-4x | | 6(4x-8)=5(5x+4) | | -2(8w-4)+6w=-2(w+5) | | 5(3x-1)=8x+10 | | X√2+2x-3=0 | | 2y-1+2(3y+2)=-4(y+3) | | -4x+2=3x+16 | | -2=y/4 | | 7(x-2)=6x+1-3(-3x-1) | | 3y+84=60 | | (x-12)=132 | | -4(-5x+4)-3x=2(x-1)-5 | | 4(u+4)=-3(4u-4)+8u | | (0.20)(10)=0.05(10)+0.40(10–x | | 1+12=n | | 51+34=x | | 6n+8=108 | | (0.20)(10)=0.05(10)+0.40(10–x) | | 59=29^x |